Factors affecting acceptance and adoption of mobile health application (MHA) - Al-Radaideh, Ahmad Tawfig (International Journal of Psychosocial Rehabilitation, 2020)
Health systems using modern Technologies i.e. Mobile Health Application (MHAs) have a deep impact on the standards of hospital services and reducing healthcare costs. The use of MHA in a society is directly proportional to the awareness and education of the society. The factors that affect MHA acceptance has been analyzed in this study usingUnified Theory of Acceptance and Use of Technology (UTAUT) framework[1]. The UTAUT model is a new tool for evaluating the integration/adoption of MHAs. We tend to formulate the propensity to using the MHA system and behavioral exercise of healthcare professionals using empirical studies and the use of the UTAUT2 model. Trust of data most important in health sector, themain aim of this research is to check and test the factors which effect the assimilation and acceptance of the MHA by the healthcare providers. The target area of this research is Jordanian hospitals using MHA. The data used in this research is gathered from healthcare professional working in hospitals of Jordan using MHA. The work presented in this research gives a clear view of which elements effect the acceptance and adoption of MHA[2][3].